vp100813_elic_VerbalForms_ne_moch - Валентина Пуяковна Силкина (Надер); Олеся Ханина (Bernard Comrie, 2010)
О.Ханина собирает с В.П.Надер глагол leqi 'не мочь': неуспешно, т.к. сначала ВП не могла вспомнить глагол, потом не могла построить с ним предложение O.Khanina collects with V.P.Nader the verb leqi 'cannot': without success, first VP could not remember the verb, then she could not form a sentence with it Language_Name: Enets Language_Region: Asia Language_Country: Russia Project_Status: Complete Year: 2007 Start_Date: 2008-02-01 End_Date: 2011-01-31 Title vp100813_elic_VerbalForms_ne_moch